Florida Bears and Beekeeping - Malcolm T. Sanford; James D. Ellis (EDIS, 2006)
Revised! ENY-105, a 3-page illustrated fact sheet by Malcolm T. Sanford and James D. Ellis, provides beekeepers with basic information about this major predator on beehives in Florida. This version updates the 1999 version with updated information on electric fencing, a comment on the Africanized honey bee, and references. Published by the UF Department of Entomology and Nematology, September 2006.